La declaración conjunta en la Cumbre de París para el Mediterráneo. Un documento claramente mejorable en asuntos de seguridad - Marquina Barrio, Antonio (UNISCI Discussion Papers, 2009)
The Union for the Mediterranean initiative launched in Paris, in July 2008, entails fundamental changes with respect the Barcelona process. The political and security chapter has been profoundly devaluated. This question could make sense in a new theoretical approach properly articulated, including possible stages and reassurances. That is not the case. The significant and clever innovations introduced in the text: strong institutionalization of the process, common projects as the backbone of the process are not well articulated in a harmonic and theoretically consistent framework linking the three traditional baskets or chapters that are maintained in the initiative Union for the Mediterranean.
Keywords: Mediterranean Union; Paris; 2008; Security